THE EFFECT OF POPULATION SIZE, OPEN UNEMPLOYMENT RATE, AND POVERTY ON ECONOMIC GROWTH IN EAST JAVA - Roiq Azmi; Hendry Cahyono (Publikasi Inspirasi Indonesia, 2025)
Economic growth is an indicator of the success of regional development, but East Java has not yet reached the RPJMN annual target. This study aims to analyze the effect of population, open unemployment rate, and poverty on economic growth. The method used is a quantitative approach with panel data, covering 38 districts / cities during 2019-2023, using secondary data from BPS. The results show that population has a positive but insignificant effect, while open unemployment and poverty have a significant negative effect. Simultaneously, the three variables have a significant effect on economic growth. This research can be a policy reference and it is recommended to develop variables and data coverage in future studies.